2019
DOI: 10.1111/pin.12850
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary melanocytic nevus – A case report with a mutation analysis of common driver oncogenes

Abstract: Nevi are benign melanocytic tumors, and some nevi are considered to develop into malignant melanomas. Most nevi arise in the skin, but nevi occasionally occur in the conjunctiva, esophageal mucosa, or at other sites. Pulmonary melanocytic nevi are extremely rare, and only one case has been reported in the literature. Here, we present a case of pulmonary melanocytic nevus, involving a BRAF gene mutation (V600E), and we discuss the potential significance of this condition as a precursor to pulmonary malignant me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Some of the authors previously reported a case of pulmonary melanocytic nevus. The nevus cells of the pulmonary melanocytic nevus exhibited a BRAF V600E mutation, but no NRAS mutations were found [18]. No BRAF mutations were detected in the 9 previously reported cases of primary malignant melanoma of the lung or our case; therefore, primary malignant melanoma of the lung might be a form of de novo cancer, rather than arise from melanocytic nevus.…”
Section: Discussionmentioning
confidence: 40%
“…Some of the authors previously reported a case of pulmonary melanocytic nevus. The nevus cells of the pulmonary melanocytic nevus exhibited a BRAF V600E mutation, but no NRAS mutations were found [18]. No BRAF mutations were detected in the 9 previously reported cases of primary malignant melanoma of the lung or our case; therefore, primary malignant melanoma of the lung might be a form of de novo cancer, rather than arise from melanocytic nevus.…”
Section: Discussionmentioning
confidence: 40%